Thermal and mechanical properties of epoxy-clay nanocomposites - Ong, Chor Tian. (2008)
The aim of this project is to compare the themal and mechanical properties of clay filled epoxy nanocomposite with unfilled material. The materials tested are epoxy Araldite LY5052 and hardener Araldite HY5052 with Nanocor I30TC clay. The epoxy resin was mixed with the organophilic clay, in varied proportion of 0, 1.5, 2.5, 5 and 7.5 wt% with respect to 100% of the epoxy resin. The epoxy clay nanocomposites are prepared via melt intercalation to create a favourable intercalation of the prepolymer.